2020
DOI: 10.1080/17487870.2020.1785297
|View full text |Cite
|
Sign up to set email alerts
|

Crisis, what crisis? Industrial strategies and path dependencies in four European countries after the crash

Abstract: This paper asks to what extent recent European industrial policies were responses to an episode of crisis rather than more enduring policy changes in response to globalization and the knowledge-economy. We argue that the 2008 crisis and recent protectionist efforts provided policy-makers greater freedom of maneuver but structural policy reform was already underway in the 2000s. We find policy responses were shaped by three factors: policy legacies; a country's position in global value chains; or differing stat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 36 publications
1
4
0
Order By: Relevance
“…On the other hand, depending on the policy itself, certain lag periods occur regarding the manifestation of policy effects [45]. Our results support Garcia and Coulter's study that policy outcomes can be either short-term politicised remedies or enduring policy changes, and that policy responses varied significantly in terms of coherence and long-term impact [26]. Previous research has confirmed that if policy makers are only concerned about recent policy benefits and that this shortsightedness provokes inefficient public policy [46,47].…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…On the other hand, depending on the policy itself, certain lag periods occur regarding the manifestation of policy effects [45]. Our results support Garcia and Coulter's study that policy outcomes can be either short-term politicised remedies or enduring policy changes, and that policy responses varied significantly in terms of coherence and long-term impact [26]. Previous research has confirmed that if policy makers are only concerned about recent policy benefits and that this shortsightedness provokes inefficient public policy [46,47].…”
Section: Discussionsupporting
confidence: 83%
“…Craig (2015) also demonstrated that the increasing impact of industrial policy in optimising industrial structure [25]. Garcia and Coulter (2020) investigated the policy responses to industrial policy in four European countries and found significant differences and malleability of policies in terms of long-term impacts [26]. Vrolijk (2021) justified that inadequate policy implementation would hinder the industrial upgrading of underdeveloped economies and the findings implied that industrial policy needed to be improved and reconfigured [27].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Like the Eastern countries, the two Iberian states jumped on the post-GFC European bandwagon of reindustrialisation to stimulate their export sectors. In 2014, the Spanish Ministry of Industry published the ‘Agenda for strengthening the industrial sector’ and adopted an Industry Action Plan, which, however, remained ‘long on rhetoric but short on ambition’ (Garcia Calvo and Coulter, 2022: p. 204) mainly because of the government’s highly limited space for fiscal manoeuvre. The Spanish plan established six broad priority areas, but the measures rather aimed at streamlining processes and reducing costs instead of a general renovation, thus there was no break with institutional structures inherited from the past (Garcia Calvo and Coulter, 2022).…”
Section: Challenges To Economic Upgrading and Post-crisis State Aid P...mentioning
confidence: 99%
“…In 2014, the Spanish Ministry of Industry published the ‘Agenda for strengthening the industrial sector’ and adopted an Industry Action Plan, which, however, remained ‘long on rhetoric but short on ambition’ (Garcia Calvo and Coulter, 2022: p. 204) mainly because of the government’s highly limited space for fiscal manoeuvre. The Spanish plan established six broad priority areas, but the measures rather aimed at streamlining processes and reducing costs instead of a general renovation, thus there was no break with institutional structures inherited from the past (Garcia Calvo and Coulter, 2022). In its new roadmap for industrial policy until 2030, the ministry admitted that the previous government plan was not successful, which is also reflected in the declining Spanish industrial performance demonstrated in Figure 2.…”
Section: Challenges To Economic Upgrading and Post-crisis State Aid P...mentioning
confidence: 99%
“…Some scholars believe that the upgrading of the industrial structure in China is largely driven by its national policies [19]. Although the long-term impacts of relevant policies of developed countries in Europe and the United States are significantly different [20], a consensus has been generally reached by policy practitioners that policy-driven industrial structure upgrading can maximize the potential competitive advantages of different industries, thereby promoting the sustainable and green development of global economies [21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%